KOORDINASI DALAM PENGELOLAAN TRANSMIGRASI DI KELURAHAN PANGMILANG KECAMATAN SINGKAWANG SELATAN - Irvani E.01107055, Andri (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The issue regarding the handling of land titles to residents in the Village Pangmilang transmigrationSouthern District singkawang related to directing activities, integrating activities and unity of agencywork in coordination. This research uses qualitative research and do pendeskriptifan in depth, as well asthe methods used to help the research is done by observation, interview guides and documentation. Theresults of this study found that the lack of coordination of various parties or work units involved in theissue of land titles transmigration citizens whether it be land, Land courtyardÂ Keyword : directing the activities, integrating activities, employment the unity institution